Estrategia para la comercialización de cacao (Theobroma cacao) fino de aroma en la Provincia de Los Ríos - Alava Lamilla, Jefferson Joel (2023)
The plan outlined in the document is for the Province of Los Ríos to market fine aroma cocoa (Theobroma cacao). The objective is to outline the tactics for the commercialization of high-quality aroma cocoa (Theobroma cacao) in the Province of Los Ríos. The findings show that the establishment of factories for the production of intermediate goods using Ecuadorian cocoa beans as a superior raw material has not encouraged national and/or foreign investment, and that those who benefit from the low price of raw materials harvested in the Ecuador province of Los Ríos are due to the high natural agroecological potential for the production of fine aroma cocoa. A small portion of producers sell their cocoa through associations, where they are compensated with prices above market prices and also receive technical support. The strategies are to increase production per hectare and thus scientifically improve the current production yield of 6 to 8 quintals per hectare, conduct seminars for farmers; to avoid mixing fine aroma cocoa with normal cocoa, avoid exporting it; develop a more robust replacement strategy for obsolete cocoa plantations that have not been rehabilitated; and identify the best locations to grow the crop based on scientific studies.